Medications and Food Interfering with the Bioavailability of Levothyroxine: A Systematic Review - Liu H; Lu M; Hu J; Fu G; Feng Q; Sun S; Chen C (Dove Medical Press, 2023)
Hanqing Liu,1,* Man Lu,1,* Jiawei Hu,1 Guangzhao Fu,2 Qinyu Feng,3 Shengrong Sun,1 Chuang Chen1 1Department of Breast and Thyroid Surgery, Renmin Hospital of Wuhan University, Wuhan, Hubei, 430060, People's Republic of China; 2Department of Cardiology, Renmin Hospital of Wuhan University, Wuhan, Hubei, 430060, People's Republic of China; 3Department of Orthopedics, Zhongnan Hospital of Wuhan University, Wuhan, Hubei, People's Republic of China*These authors contributed equally to this workCorrespondence: Chuang Chen; Shengrong Sun, Department of Breast and Thyroid Surgery, Renmin Hospital of Wuhan University, Wuhan University, Jiefang Road 238, Wuhan, 430060, People's Republic of China, Tel/Fax +86 27 88041911, Email chenc2469@163.com; sun137@sina.comPurpose: Levothyroxine is a common prescribed drug. Many medications and food, however, can interfere with its bioavailability. The aim of this review was to summarize the medications, food and beverages that interact with levothyroxine and to assess their effects, mechanisms and treatments.Methods: A systematic review on interfering substances that interact with levothyroxine was performed. Web of Science, Embase, PubMed, the Cochrane library, grey literature from other sources and the lists of references were searched for human studies comparing the levothyroxine efficacy with and without interfering substances. The patient characteristics, drug classes, effects and mechanism were extracted. The NHLBI study quality assessment tools and the JBI critical appraisal checklist were used to assess the quality of included studies.Results: A total of 107 articles with 128 studies were included. Drugs interactions were revealed in calcium and iron supplements, proton pump inhibitors, bile acid sequestrants, phosphate binders, sex hormones, anticonvulsants and other drugs. Some food and beverage could also induce malabsorption. Proposed mechanisms included direct complexing, alkalization, alteration of serum thyroxine-binding globulin levels and acceleration of levothyroxine catabolism via deiodination. Dose adjustment, administration separation and discontinuation of interfering substances can eliminate the interactions. Liquid solutions and soft-gel capsules could eliminate the malabsorption due to chelation and alkalization. The qualities of most included studies were moderate.Conclusion: Lots of medications and food can impair the bioavailability of levothyroxine. Clinicians, patients and pharmaceutical companies should be aware of the possible interactions. Further well-designed studies are needed to provide more solid evidence on treatment and mechanisms.Keywords: L-T4, drug, interference, malabsorption, side effect, solution